Hypoxic mesenchymal stem cell-derived exosomes promote bone fracture healing by the transfer of miR-126. (February 2020) - Liu, Wei; Li, Linwei; Rong, Yuluo; Qian, Dingfei; Chen, Jian; Zhou, Zheng; Luo, Yongjun; Jiang, Dongdong; Cheng, Lin; Zhao, Shujie; Kong, Fanqi; Wang, Jiaxing; et al.
Abstract: Increasing evidence has suggested that paracrine mechanisms might be involved in the underlying mechanism of mesenchymal stem cells (MSCs) transplantation, and exosomes are an important component of this paracrine role. However, MSCs are usually exposed to normoxia (21% O2 ) in vitro but experience large differences in oxygen concentration in the body under hypoxia. Indeed, hypoxic precondition of MSCs can enhance their paracrine effects. The main purpose of this study was to determine whether exosomes derived from MSCs under hypoxia (Hypo-Exos) exhibit greater effects on bone fracture healing than those under normoxia (Exos). Using in vivo bone fracture model and in vitro experiments including cell proliferation assay, cell migration assay and so on, we confirmed that Hypo-Exos administration promoted angiogenesis, proliferation and migration to a greater extent when compared to Exos. Furthermore, utilizing a series in vitro and in vivo gain and loss of function experiments, we confirmed a functional role for exosomal miR-126 in the process of bone fracture healing. Meanwhile, we found that knockdown of hypoxia inducible factor 1 (HIF-1α) resulted in a significant decrease of miR-126 in MSCs and exosomes, thereby abolishing the effects of Hypo-Exos. In conclusion, our results demonstrated a mechanism by which Hypo-Exos promote bone fracture healing through exosomal miR-126. Moreover, hypoxia preconditioning mediated enhanced production of exosomal miR-126 through the activation of HIF-1α. Hypoxia preconditioning represents an effective and promising method for the optimization of the therapeutic actions of MSC-derived exosomes for bone fracture healing. Statement of significance: Studies have confirmed that transplantation of exosomes exhibit similar therapeutic effects and functional properties to directly-transplanted stem cells but have less significant adverse effects. However, during in vitro culture conditions, MSCs are usually exposed to normoxia (21% O2 ) which is very different to the oxygen concentrations found in the body under natural physiological conditions. Our results demonstrated a mechanism by which Hypo-Exos promote bone fracture healing through exosomal miR-126 and the SPRED1/Ras/Erk signaling pathway. Moreover, hypoxia preconditioning mediated enhanced production of exosomal miR-126 through the activation of HIF-1α. Hypoxia preconditioning represents an effective and promising method for the optimization of the therapeutic actions of MSC-derived exosomes for bone fracture healing. Graphical abstract: Image, graphical abstract